PENINGKATAN PRODUKSI IKAN KONSUMSI BERBASIS KEARIFAN LOKAL DENGAN TEKNOLOGI CULTURE BASED FISHERIES ( CBF) DI MA BAHRUL ULUM MULIASARI, BANYUASIN - Rahma Mulyani; Sumantriyadi Sumantriyadi; Lia Perwita Sari; Yulia Puspita Sari; Santi Mayasari; Humairani Humairani (Jurnal Abdi Insani, 2022)
One of the aquaculture techniques is Culture Based Fisheries (CBF). CBF or Cultivation-Based Capture Fisheries is a capture fishery activity where the caught fish come from cultured fish seeds that are spread into water bodies, and the stocked fish seeds will grow by utilizing available natural food in increasing consumption fish production based on local wisdom. The purpose of this activity is to add insight and information for teachers and students about aquaculture using the CBF technique. The method used is the observation and preparation stage, the coordination stage, the tool and material preparation stage, and finally the implementation stage. The results of PKM activities The target audience in this Community Service activity is the community in general, but specifically it is addressed to the Santri/Students and Teachers at MA Bahrul Ulum Muliasari Tanjung Lago, Banyuasin Regency, which specifically has been attended by 41 people. During the PKL implementation, activities were carried out in 3 activities, the first was a speech from the head of MA Bahrul Ulum and also the PKL Team Leader, in the second session followed by a presentation session of 6 materials and the last was a demonstration activity or practice of measuring water quality as well as socialization of aquaculture study programs. fish. The results of this PKM are used to increase the willingness and knowledge of the community through students/teachers in developing their area to apply CBF technology to develop the fisheries sector in the area which looks quite promising.